Sustaining Remote Connections through personalised English language speaking practice (SRC) / Nurul Kamalia Yusuf ... [et al.] - Yusuf, Nurul Kamalia; Megat Abdul Rahim, Puteri Rohani; Abd Rahman, Mohd Farhan; Mohd, Thuraiya; Mahyuddin, Muhammad Naim; Hasbullah, Mohd Nasurudin (2022)
Remote learning has left an emotional impact that leads to anxiety. A high number of students are reported to deal with various online learning constraints. This has led to an increase in speaking anxiety among students. They need external validation to reduce anxiety. Teacher plays a role in creating a sense of belonging. Hence, the idea of this innovation is to make remote learning not only bearable but also a learning space that makes students feel valued and included. The need analysis prior to ideating SRC was carried out. The personalized learning template and video or Sustaining Remote Connections through Personalized Speaking Practice (SRC) provides a platform to start learning common English vocabulary, phrases, and dialogues. The interactive templates and videos are integrated in three stages of speaking lessons: pre-speaking, while speaking and post-speaking. SRC comes with a personalized feature that enables teachers to connect with their students by adding their names and elements that are related to their culture in the choice of vocabulary and dialogues. SRC comprises three phases that start with English vocabulary exercises that help students retain the basic vocabulary. It is followed by phrases and dialogues for beginners that include greeting, introducing self and others, asking, and responding to where they live and which country they come from, asking how people spend their free time, and talking about holidays, activities, health, etc. SRC is an opportunity to make speaking lessons supportive especially among the low-proficiency students in areas with low internet connection.